Temperature and Activity of Litter Skinks (Reptillia: Scincidae: Eutropis) at Kubah National Park, Sarawak (Borneo) - Veronica, Martin (Universiti Malaysia Sarawak (UNIMAS), 2017)
The effects of environmental (ambient) temperature on body temperature, as well as the resulting activity of two species of skinks of the genus Eutropis (E rudis and E. multtfosciata) were examined at Kubah National Park, southern Sarawak, East Malaysia (Borneo), from September 2016 to March 2017. Visual Encounter Surveys were made along line transects. Species were identified and three types of temperature (surface body temperature, substrate temperature and ambient temperature) recorded. The relationship between the reptile body temperature and environmental temperatures was analysed using regression and correlation analyses, with SPSS software. Results show that both ambient temperature and substrate temperature are significantly related to body temperature of both Eutropis species. Eutropis multtfosciata appears to be a better heliotherm while Eutropis rudis is a thigmotherm